Uncovering coal mining accident coverups: An alternative perspective on China's new safety narrative. (April 2022) - Yang, Xiuyun; Krul, Kees; Sims, David
Highlights: This study employs a novel dataset of 180 coverups cases of mining accidents derived from official, judicial and media sources. The dataset indicates that China's safety measures are structurally compromised and deliberately manipulated. Failing regulatory, monitoring, and sanctioning measures have led to an unreliable estimate of mining accidents and fatalities. This study cast doubts about the conceived success of China's new safety narrative. Abstract: China has taken on a series of comprehensive institutional measures to improve the safety of its coal mining industry and workers. Official figures indicate similar reductions to both accidents and fatalities, from which a "new safety narrative" has emerged in official discourses. However, this view neglects the fact that many accidents are concealed or underreported in China's mining sector. This study critically examines China's safety measures with a novel dataset of 180 mining accident coverup cases derived from official, judicial, and media sources. The study's findings support three observations: (i) despite the imposition of stricter regulations and the closure of many informal and small-scale mines, accident coverups have continued at both legal and large-scale mines; (ii) despite increased monitoring including the implementation of a fatality indicator system, accident reporting is consistently manipulated by mine owners, local authorities, and even victims' families; and (iii) although new stiffer penalties specifically sanction accident coverups, they are rarely imposed. Our results cast doubt on the conceived success of China's new safety narrative and demonstrate how industrial safety measures are deliberately and structurally compromised.